Sistem Informasi Manajemen Stok Berbasis Web Pada PT Sumber Rejeki Tirta - Wijaya, Hendry; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2023)
PT Sumber Rejeki Tirta is a company that provides b-one brand drinking water. However, in the process of selling, borrowing, processing and producing gallons, they still use the manual method. The purpose of this study is to design and implement a stock information system that suits the company's needs in managing data on purchases, processes, production, reuse, sales, can repair goods and recalls in order to help companies do better in doing their jobs. The system modeling uses UML (Unified Modeling Language) which consists of Use Case Diagrams, Activity Diagrams and Class Diagrams, with a waterfall design. The research resulted in a stock management information system program that was able to overcome the deficiencies contained in the previous system and was able to maximize the transaction data management process and help facilitate work at PT Sumber Rejeki Tirta